ANALYSIS OF THE APPLICATION OF GREEN ACCOUNTING ON THE FINANCIAL PERFORMANCE OF PT UNILEVER INDONESIA TBK - Amru Usman; Rina Iklima; Utia Rahmi; Safriana; Herlina BR Sihotang (RADJA PUBLIKA, 2023)
This research was written with the aim of analyzing the application of Green Accounting at PT Unilever Indonesia Tbk. The background of this writing is because the writer wants to analyze Green Accounting at PT Unilever Indonesia Tbk. The method used in this research is a qualitative research method, the data source used in this research is secondary data. Secondary data is a source of data obtained by researchers indirectly through intermediary media obtained and recorded by other parties. The results of this study indicate that PT Unilever Indonesia Tbk has implemented Green Accounting very well. The costs incurred by PT Unilever Indonesia Tbk in implementing Green Accounting in 2019 – 2021 amount to IDR 284,842,399,000. In implementing Green Accounting, PT Unilever Indonesia Tbk only focuses on 4 aspects namely; Economic Aspect, Environmental Aspect, Social Aspect, Health Aspect.